Kontribusi Efikasi Diri terhadap Academic Burnout pada Mahasiswa Semester Akhir Universitas Negeri Padang - Sepdila, Wenny; Magistarina, Elrisfa (Lembaga Yasin AlSys, 2024)
Academic burnout is a feeling of tiredness and boredom in doing tasks, pessimism about the functions assigned, and feeling ineffective as a student. The impact of academic burnout on students is the deterioration of their physical, mental, and psychological condition which can cause students to feel full and tired of doing their assignments, proposals, or theses which can result in neglect and delay in their tasks. This research aims to find out the contribution of self-efficacy to academic burnout in final semester students at Padang State University. The quantitative method is used for this research with a descriptive quantitative research type. The population for this study consisted of final semester students at Padang State University class 2018 and 2019. The sampling technique used for this study was purposive sampling with a total sample size of 95 people. The research instrument used is the Maslach Burnout Inventory Student-Survey Scale adapted into Indonesian by Arlinkasari et al. (2017) and the General Self-Efficacy Scale adapt by Novrianto et al. (2019). Hypothesis testing was carried out using simple regression analysis with a correlation coefficient (r) = -0.207 and significant results p = 0.045, meaning that there is a negative significant influence between self-efficacy on academic burnout in final semester students. It can be concluded that the higher the self-efficacy of final semester students at Padang State University, the lower the academic burnout.